2014
DOI: 10.1186/1532-429x-16-33
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular outcome associations among cardiovascular magnetic resonance measures of arterial stiffness: the Dallas heart study

Abstract: BackgroundCardiovascular magnetic resonance (CMR) has been validated for the noninvasive assessment of total arterial compliance and aortic stiffness, but their associations with cardiovascular outcomes is unknown. The purpose of this study was to evaluate associations of CMR measures of total arterial compliance and two CMR measures of aortic stiffness with respect to future cardiovascular events.MethodsThe study consisted of 2122 Dallas Heart Study participants without cardiovascular disease who underwent CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 42 publications
2
51
1
1
Order By: Relevance
“…Therefore, patients with lesser aortic distensibility or increasing LV mass are more vulnerable to repetitive HD-induced cardiac ischemia (43,44). The preserved aortic distensibility over 12 months in the intervention group compared with significant reductions in the control group may have contributed to the observed cardiac effects (22,32). The interactions between intradialytic events and fluid/volume status are complex, and additional investigations are warranted to understand the mechanisms by which dialysate cooling might attenuate the progression of cardiomyopathy in patients on HD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, patients with lesser aortic distensibility or increasing LV mass are more vulnerable to repetitive HD-induced cardiac ischemia (43,44). The preserved aortic distensibility over 12 months in the intervention group compared with significant reductions in the control group may have contributed to the observed cardiac effects (22,32). The interactions between intradialytic events and fluid/volume status are complex, and additional investigations are warranted to understand the mechanisms by which dialysate cooling might attenuate the progression of cardiomyopathy in patients on HD.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic distensibility analysis is depicted in Figure 1, E and F as previously described (22). The ascending thoracic aortic area was manually traced using Jim version 6 (Xinapse software, UK) and graphically represented against time.…”
Section: Aortic Distensibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…[83,84] In addition, CMR may be used as an alternative technique to evaluate aortic stiffness, which is strongly related to systolic hypertension and is associated with future cardiovascular events. [85,86] Although sensitivity of CMR is high, the specificity is moderate for detecting major coronary artery lesions, and the availability and costs of CMR equipment currently limit large-scale use. [45] Another problem is the uncertainty of translating abnormal CMR findings observed at a young age to actual later-life CVD event risks, as longitudinal studies with sufficient follow-up time are not available.…”
Section: Coronary Artery Calcium Scorementioning
confidence: 99%
“…The predictive value of PWV has been assessed in a substudy of the Dallas Heart Study in 2122 healthy subjects with an 8-year follow-up period [3]. The study showed CMR-derived PWV to be associated with the occurrence of cardiovascular events and improved risk stratification when added to the Framingham Risk Score.…”
mentioning
confidence: 99%